Roman C. answered • 11/26/12

Masters of Education Graduate with Mathematics Expertise

Start by solving the first equation for x.

x - 4y = -19

x = 4y - 19

Now plug this in the second equation.

3y - 8x = 65

3y - 8(4y - 19) = 65

3y - 32y + 152 = 65

-29y = 65 - 152 = -87

y = -87 / -29 = 3

Plug this in the first equation.

x = 4y - 19 = 4*3 - 19 = -7

So x = -7, y = 3 is the solution.

We can check this answer:

x - 4y = -19

-7 - 4(3) = -19

-7 - 12 = -19

-19 = -19

and

3y - 8x = 65

3(3) - 8(-7) = 65

9 + 56 = 65

65 = 65